Observable Signatures of Classical T Tauri Stars Accreting in an Unstable Regime - Kurosawa Ryuichi; Romanova M. M. (EPJ Web of Conferences, 2014)
We discuss key observational signatures of Classical T Tauri stars (CTTSs) accreting through Rayleigh-Taylor instability, which occurs at the interface between an accretion disk and a stellar magnetosphere. In this study, the results of global 3-D MHD simulations of accretion flows, in both stable and unstable regimes, are used to predict the variability of hydrogen emission lines and light curves associated with those two distinctive accretion flow patterns. In the stable regime, a redshifted absorption component (RAC) periodically appears in some hydrogen lines, but only during a fraction of a stellar rotation period. In the unstable regime, the RAC is present rather persistently during a whole stellar rotation period, and its strength varies non-periodically. The latter is caused by multiple accreting streams, formed randomly due to the instability, passing across the line of sight to an observer during one stellar rotation. This results in the quasi-stationarity appearance of the RAC because at least one of the accretion stream is almost always in the line of sight to an observer. In the stable regime, two stable hot spots produce a smooth and periodic light curve that shows only one or two peaks per stellar rotation. In the unstable regime, multiple hot spots formed on the surface of the star, produce the stochastic light curve with several peaks per rotation period.